Harvesting the Gas Molecules by Bioinspired Design of 1D/2D Hybrids Toward Sensitive Acetone Detecting. Issue 3 (16th December 2022) - Yan, Muyu; Gao, Xiaoping; Han, Xiao; Zhou, Danni; Lin, Yue; Chen, Wenxing; Xue, Zhenggang; Wu, Yuen
Abstract : Single‐atom catalysts (SACs) are highly attractive in many surface‐dependent reactions due to their extraordinary reactivity and maximum atomic efficiency. However, in a practical catalytic system, guiding and transferring the reactant molecules to target single‐atom sites are crucial processes for achieving high‐efficient reactions. Herein, gas‐microchannels on TiO2 nanorod‐supported Pt single‐atom catalyst by in situ growing derivative TiO2 nanosheets are constructed. Those perpendicular‐grown TiO2 nanosheets can guide gas molecules to the reactive single Pt sites and thus realize an intact system of guidance‐transfer‐reaction. Experimentally, the local coordination and electronic states of Pt species decrease with the growth of nanosheets, which could significantly strengthen the adsorption and activation of oxygen molecules toward the acetone sensing. The final Pt1 /TiO2 catalysts exhibit a high sensing response (13.6–50 ppm) to acetone gas, which are approximately three times higher than that of catalysts without scaly shell (4.8–50 ppm). Abstract : A TiO2 nanorod‐supported Pt single‐atom catalyst with abundant microchannels and 1D/2D heterointerfaces on the surface is presented. The specific surface structure can harvest and guide the reactant molecules to the reactive single Pt sites and thus realize high reactivity and high accessibility. The Pt1 /TiO2 NRs@NSs catalysts exhibit high sensitivity and excellent stability toward acetone sensing.